Preparation method of porous carbon for silicon-carbon negative electrode material
By using fluidized bed equipment to activate pore formation in the preparation of porous carbon materials, combined with the pulverization and grading, washing and carbonization steps, the problems of uneven particle size and low activation efficiency are solved, and the pore structure of silicon carbon anode material is improved Uniformity and yield rate reduce production costs and achieve efficient preparation of porous carbon materials.
Patent Information
- Application Number
- CN202411813666.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-12-11
AI Technical Summary
In the preparation process of existing porous carbon materials, there are problems such as uneven particle size, low activation efficiency, overactivation, high metal pollution prevention and control costs and low yield, which is difficult to improve the pore structure uniformity and production of silicon carbon negative electrode materials. efficiency.
The fluidized bed equipment is used to activate the pore formation, combine the pulverization and grading, washing and carbonization steps, use water vapor or CO2 as the activation gas, control the activation temperature and time, perform pulverization and grading in advance, and purify it using an acid solution during the washing process. Reduce the carbonization temperature to improve the mass and yield of porous carbon.
The efficiency and uniformity of the activation reaction are improved, the overactivation phenomenon is avoided, the production cost is reduced, the pore structure uniformity and yield of porous carbon are improved, and the quality and safety of battery materials are enhanced.
Smart Images

Figure CN119263278A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lithium ion battery negative electrode materials, and specifically relates to a method for preparing porous carbon for silicon-carbon negative electrode materials. Background Art
[0002] With the rapid development of lithium-ion automobiles, electronics and other industries, the requirements for battery energy density are getting higher and higher. At present, due to the high theoretical specific capacity of silicon-based negative electrode materials, it is considered to be the first choice for the next generation of high-capacity lithium-ion battery negative electrode materials. Among them, the embedded silicon-carbon negative electrode is one of the earliest commercialized silicon-carbon negative electrode materials, and silicon particles are usually embedded in a continuous carbon matrix. Therefore, the pore structure of the carbon matrix can effectively affect the structural stability and cycle life of the material.
[0003] As a kind of carbon matrix, porous carbon has the advantages of high specific surface area, pore volume, good chemical stability and cyclic stability, and is widely used in the field of energy storage. The traditional porous carbon production process is mostly: the selected biomass raw materials are carbonized and converted into carbon materials through high-temperature pyrolysis; the carbonized materials are crushed to less than 1mm; the materials after coarse crushing need to be activated to increase their specific surface area and pore structure. The commonly used activation method is in a rotary kiln, KOH and other carbon materials react at high temperature to expand their pore size; after activation, the product is washed and purified to remove residual impurities in the material; in an inert atmosphere, the washed and impurity-free material is calcined at high temperature to remove possible functional groups in the material and stabilize the pore structure; the material is crushed by air flow mill, mechanical mill, etc., and then the qualified products are screened out by classification.
[0004] However, with the practical application of the above method, some difficult-to-solve technical problems have also emerged: 1. The particle size of the material after coarse crushing is uneven, and the particle size, shape and specific surface area vary greatly between the particles. In order to ensure the activation effect during activation in the rotary kiln, the required activation time is long and the activation efficiency is low; during the long activation process, the material is prone to over-activation, that is, over-corrosion, resulting in the phenomenon of porous carbon pores, broken holes, perforations, etc., the activation effect is not good, and the product yield is directly reduced; further, if the material is crushed to a smaller particle size before activation, it will make it easier to over-activate in the subsequent activation, and the activation process is extremely difficult to control. 2. The particle size of the material after coarse crushing is uneven, and the particle size, shape and specific surface area vary greatly between the particles. Under the same activation time, it also leads to high uneven particle activation and poor activation effect; and in the subsequent processing of large particle materials after activation to the finished product particle size, the pore structure will inevitably be destroyed (such as broken holes, perforations, etc.) due to the crushing, which will further lead to a decrease in the uniformity of the pore structure of the porous carbon finished product and a decrease in the yield. 3. The activated material is still in the state of large particles, and it is not easy to remove impurities inside the particles during washing; and the center of the large particles may not be fully activated, resulting in low quality of the finished product after crushing. 4. Battery materials need to prevent metal contamination, so the lining of porous carbon crushing equipment generally needs to be ceramicized, and the equipment cost is high. However, as the crushing efficiency is higher than that of air flow mills and mechanical impact mills, it is difficult to achieve ceramic linings for equipment such as ring roller mills, so they are rarely used, and porous carbon cannot be processed efficiently and at low cost; 5. The particle size and particle size distribution requirements of general qualified products are very strict, so the requirements for the classifier are very high. When the particle size is very fine, the efficiency of the classifier will also be reduced accordingly, and the classification of fine particles of 2um and above will fail, that is, in order to remove fine particles of 2um and above, some coarse qualified particles of 2um and above will be lost; 6. The aforementioned traditional process defects limit the yield of porous carbon products to between 10-15%, which is relatively low and difficult to effectively improve.
[0005] Therefore, there is an urgent need to provide a method for preparing porous carbon for silicon-carbon negative electrode material to solve the above problems. Summary of the invention
[0006] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a method for preparing porous carbon for silicon-carbon negative electrode materials, while solving the technical problems that the yield of porous carbon for silicon-carbon negative electrode materials is difficult to improve, the activation process is difficult to control, the activation efficiency is low, the activation effect is poor, and the cost of metal pollution prevention and control is high, while further improving the uniformity of the pore structure of porous carbon for silicon-carbon negative electrode materials, improving the quality of porous carbon, improving production efficiency, and reducing production costs.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions: A method for preparing porous carbon for silicon-carbon negative electrode material, comprising the following steps: crushing and grading, activating and forming pores, washing, and carbonizing; The method of crushing and classifying is that the pyrolysis carbonized material is crushed and classified to obtain crushed and classified material; The pyrolysis carbonized material is prepared by using biomass raw materials and / or non-biomass raw materials; The activation pore-forming method is to perform activation pore-forming treatment on crushed and classified materials in a fluidized bed device in the presence of an activation gas to obtain an activated pore-forming material.
[0008] Preferably, in the crushing and classification, the particle size specifications of the crushed and classified materials are D10≥2um, D50: 5-10um, D90≤15um, and Dmax≤25um.
[0009] Preferably, in the activation pore making, the activation gas is at least one of the following: water vapor, CO2.
[0010] Preferably, in the activation pore-forming process, the activation pore-forming temperature is 800-1100° C., and the activation pore-forming time is 1-5 h.
[0011] Furthermore, when the pyrolysis carbonized material is prepared by using non-biomass raw materials and / or biomass raw materials, the crushing and classification step further includes: pyrolysis carbonization; The pyrolysis carbonization method is to perform pyrolysis carbonization treatment on non-biomass raw materials / or biomass raw materials under the protection of inert gas to obtain pyrolysis carbonized materials.
[0012] Furthermore, when the pyrolysis carbonization material is prepared using biomass raw materials, or using biomass raw materials and non-biomass raw materials, the crushing and classification step also includes: steam explosion, pyrolysis carbonization; The steam explosion method comprises: performing steam explosion treatment on the biomass raw material in the presence of water vapor to obtain a steam-exploded material; The pyrolysis carbonization method is to perform pyrolysis carbonization treatment on the steam explosion material under the protection of inert gas to obtain the pyrolysis carbonized material; or to mix the steam explosion material with non-biomass raw materials to perform pyrolysis carbonization treatment to obtain the pyrolysis carbonized material.
[0013] Furthermore, when the pyrolysis carbonized material is prepared using biomass raw materials, the crushing and classification step also includes: steam carbonization and steam explosion; The steam carbonization method is to perform steam carbonization treatment on the biomass raw material in the presence of water vapor; The steam explosion method is that after the steam carbonization is completed, the steam carbonization temperature is kept unchanged, and the pressure is released to perform steam explosion to obtain the pyrolysis carbonized material.
[0014] Furthermore, the activated pore-forming material is washed and carbonized to obtain porous carbon for silicon-carbon negative electrode material.
[0015] Furthermore, the washing method is to completely immerse the activated pore-forming material in hydrochloric acid or a mixed acid solution, and after heating the immersion, wash it to neutrality, and dry it to obtain a purified material.
[0016] Preferably, the mass fraction of the hydrochloric acid solution is 5-20%.
[0017] Preferably, the mixed acid is at least two of hydrochloric acid, nitric acid, sulfuric acid and hydrofluoric acid.
[0018] Furthermore, the carbonization method is to carbonize the purified material obtained by washing under the protection of an inert gas, control the high-temperature carbonization temperature to be not less than 1000° C., and obtain porous carbon for silicon-carbon negative electrode material.
[0019] Compared with the prior art, the present invention has the following beneficial effects: (1) The method for preparing porous carbon for silicon-carbon negative electrode material of the present invention uses a fluidized bed instead of a rotary kiln in the traditional process to activate and pore the material after pyrolysis and carbonization. The carbon material particles in the fluidized bed are in a suspended motion state, which greatly increases the contact area between the particles and the gas, and the particles are constantly mixed and tumbled in the bed layer, so that the activator can fully contact the material, thereby increasing the diffusion rate of the activator into the material, making the activation reaction more sufficient and improving the efficiency of the activation reaction. The violent movement of the particles in the fluidized bed makes the temperature distribution in the bed more uniform. On the one hand, the rapid heat exchange between the gas and the particles ensures that the particles can quickly obtain the heat required for the activation reaction, so that the activation reaction proceeds under suitable temperature conditions; on the other hand, the uniform temperature distribution can avoid the occurrence of local overheating or overcooling, reduce the product quality differences caused by uneven temperature, and improve the stability of product quality. The fluidized state of the solid particles in the fluidized bed makes them more evenly distributed in the bed layer, and each particle has a similar movement trajectory and residence time. This makes the activation conditions experienced by each particle basically the same, including the concentration of the activator, reaction temperature, reaction time, etc., thereby ensuring the uniformity of the activation reaction in the entire material system, and the quality of the final product is more uniform and stable. Compared with the rotary kiln activation in the traditional process, the fluidized bed can effectively avoid the accumulation and blockage of materials in the reactor, reduce the situation of local over-activation or under-activation caused by uneven material distribution, and improve the activation effect and quality stability of the product.
[0020] (2) Since the material is not uniformly activated in the rotary kiln when using a rotary kiln for activation and pore making, it is easy to cause the problem of over-activation of the material. Therefore, in the traditional process, before using the rotary kiln for activation and pore making, the material is only coarsely crushed, and the material particle size is relatively large to reduce the influence of over-activation. At the same time, due to the large particle size of the material, in order to improve the activation efficiency, potassium hydroxide is often used as an activator during activation. Despite this, it still takes a long activation time to achieve a good activation effect, and the activation efficiency is low. In addition, due to the use of potassium hydroxide as an activator, a large amount of purified water is required in the subsequent washing and purification stage to wash it to neutrality. In order to solve the problems of long activation time, low activation efficiency, large environmental pollution and waste of water resources in the subsequent washing and purification process that are inevitable when using a rotary kiln for activation and pore making, the present invention uses a fluidized bed for activation and pore making. The activation reaction is carried out evenly in the entire material system, which effectively improves the control of the activation process. Therefore, it can be directly crushed and graded to a particle size close to the final porous carbon product before activation and pore making, effectively avoiding the problem of over-activation of the material during activation. At the same time, the energy required for activation of materials with small particle sizes is relatively small, and due to the increase in the reaction area, the activation pore-forming time is significantly shortened, and the activation pore-forming efficiency is improved. Therefore, when the present invention uses a fluidized bed for activation pore-forming, water vapor and / or carbon dioxide can be used as an activator for activation pore-forming, which can improve the activation pore-forming efficiency, reduce the activation energy consumption, improve the activation effect, and avoid the waste of water resources in the washing and purification process.
[0021] (3) Based on the advantages of fluidized bed activation pore formation, such as high efficiency, short time, easy control of activation process, low degree of overactivation and good product uniformity, the present invention replaces the coarse crushing step in the traditional process by crushing and grading, directly crushing and grading the material after pyrolysis and carbonization to a final particle size close to the porous carbon requirement, and the material after subsequent high-temperature carbonization no longer needs to be crushed and graded, and the finished product is directly obtained. In the traditional process, the crushing and grading step is the last step in the preparation of carbon materials. Since the porous carbon material has a particle size requirement of D0 ≥ 2μm, it is difficult to achieve with commonly used grading equipment. Therefore, if the particle size of the final product is to meet the requirements, a part of the material that meets the particle size requirements and the small particles that do not meet the particle size requirements must be removed together. In addition, the grading efficiency is relatively low at this time, resulting in a lower yield of the final product. In the process proposed by the present invention, because the activation pore-forming process will corrode part of the particles, so that the particle size is further reduced, the crushing and grading step only needs to be crushed to a particle size close to the required particle size of the finished product. After the activation reaction, the material that is originally close to the required particle size of the finished product can meet the particle size requirement of the finished product, thereby effectively reducing the grading requirements for the grading equipment, thereby improving the efficiency of crushing and grading, and effectively improving the yield of the final product.
[0022] (4) Since the crushing and grading step is carried out before the washing and purification step, the selection of crushing and grading equipment does not need to consider the contamination of the equipment material to the material, because even if metal impurities are introduced, they can be removed by acid washing in the washing and purification step. Therefore, equipment with high crushing and grading efficiency or more economical but not easy to prevent metal contamination can be selected, such as: ring roller mill, so as to further improve the yield of this step and the final output; in addition, moving the crushing and grading step forward can also avoid the pore structure damage of the activated large particles during the subsequent crushing to the porous carbon product particle size, such as broken holes, perforations, etc., effectively improving the uniformity of the pore structure of the porous carbon material and ensuring the quality and yield of the finished product.
[0023] (5) During the fluidized bed activation pore-forming and washing purification process, ultrafine powders (such as 1 um or finer) that do not meet the product particle size requirements can be further removed, thereby further improving the quality of porous carbon products, as well as the safety of the subsequent fluidized bed chemical vapor deposition process for preparing silicon-carbon negative electrode materials and the quality of the final product. These ultrafine powders have small particle size and large specific surface area, so there is a strong van der Waals force and surface energy between the particles, resulting in small particles tightly agglomerated together or adsorbed on large particles. In the traditional process, it is difficult to remove them cleanly by using air flow classification in the crushing and classification stage. The large specific surface area of these small particles can provide more active sites in the CVD reaction. These sites will catalyze chemical reactions, making the reaction rate faster. A large amount of reaction heat is quickly released in a short time, which will cause the temperature to rise sharply and cause runaway. In addition, during the CVD process, Si-C bonds will be formed between carbon and silicon, and a large amount of heat will be released during the bonding process. The heat transfer between the agglomerated small particles is hindered, and the reaction heat inside the agglomerate cannot be effectively dissipated, which will form a high-temperature area inside the agglomerate, causing runaway. This causes certain quality and safety issues in the CVD process. In addition, since the fluidized bed has a certain classification effect during the activation pore-making and washing purification process, the crushing and classification step can reduce the requirements for the particle size distribution of the material, so that the crushing and classification stage can maintain a higher yield; (6) For pyrolysis carbonized materials prepared from biomass raw materials, pre-treating the raw materials by steam explosion or steam explosion plus carbonization before pyrolysis carbonization will improve the reaction efficiency of subsequent processes and improve the uniformity and stability of the cell structure of the biomass raw materials, effectively solving the shortcoming of poor batch stability of biomass raw materials, reducing the batch differences of products, and helping to ensure the long-term quality of the products.
[0024] Steam explosion improves the efficiency of subsequent process reactions: Place the material (such as wood fiber raw materials, straw and other biomass) in a closed container and pass high-temperature and high-pressure steam. The steam will gradually penetrate into the internal pores and cell wall structures of the material. Under high temperature and high pressure, the lignin and other components in the material will soften, and the hydrogen bonds between cellulose molecules will be weakened, making the overall structure of the material relatively loose, laying the foundation for the subsequent blasting process. For example, for wood raw materials, the originally dense and hard wood structure will become more easily destroyed after the steam action. When the material is fully acted on by steam in a closed container for a set time, the pressure is released instantly, and the internal high-pressure environment will rapidly change to a normal pressure environment. At this time, a huge pressure difference will be generated inside the material due to the sudden release of steam pressure. This pressure difference is like triggering countless "micro explosions" inside the material, causing the material's organizational structure to be strongly destroyed. The cell walls and other structures of the material will be broken and torn due to the rapid expansion of the internal steam. The fibers and other components that were originally closely connected will be broken up and separated. The originally large pieces of material will be broken into smaller particles or fiber bundles. The loose and fragmented physical structure formed gives it a larger specific surface area and increases the chance of contact with external substances (such as enzymes, chemical reagents, etc.). Whether it is subsequent bioconversion, chemical modification or other processing, the reaction efficiency will be significantly improved. Because the connection between cellulose, hemicellulose and lignin is broken, part of the lignin will be degraded and become some small soluble molecules, which increases the porosity and specific surface area of the biomass raw materials; steam explosion can also reduce the crystallinity of cellulose and increase the mobility of cellulose molecular chains. These advantages make it easier for the material to contact and react with the material during the subsequent pyrolysis carbonization and activation pore-making process, thereby improving the reaction efficiency.
[0025] Steam explosion improves raw material batch stability: The destructive effect of hydrogen bonds during steam explosion causes the tight connection between cellulose, hemicellulose and lignin to be untied, and lignin and hemicellulose can be more evenly dispersed around cellulose after the hydrogen bonds are broken. The originally tightly aggregated cellulose molecular chains become loose, which helps to make the internal structure of the raw material more uniform. This uniform structure is conducive to subsequent processing. For example, during the enzymatic hydrolysis process, the enzyme can contact the cellulose more evenly, because after the hydrogen bonds are broken, the surface area of cellulose increases, and the interaction between the enzyme and the substrate is more uniform, thereby improving the uniformity of the reaction. Although the hydrogen bonds are broken, some new interactions will form between the components of the raw materials during steam explosion. For example, some products produced by the hydrolysis of hemicellulose may undergo chemical cross-linking reactions with cellulose or lignin. These new connection methods replace the original hydrogen bonds to a certain extent, forming a more stable structure.
[0026] For different biomass raw materials, their original structures vary greatly, and there may be some areas with dense local structures and fewer pores. The strong impact force generated by steam explosion will destroy the cell structure of the biomass raw material, tear open and break up the fiber tissue with internal structural differences caused by factors such as the growth environment and growth cycle. The originally uneven structure tends to form a more uniform state under the action of this external force, forming a relatively uniform fibrous material. In addition, the lignin in the biomass raw material will be redistributed around the cellulose to a certain extent, forming a relatively stable supporting structure. This structure is similar to building a stable framework around the pores, making the pores less likely to collapse during subsequent processing (such as drying, storage or further chemical treatment). During the steam explosion process, the partial hydrolysis of hemicellulose and the modification of lignin help stabilize the chemical composition of the raw materials. Hemicellulose plays a role in filling and connecting cellulose microfibrils in the cell wall structure of the raw material. The hydrolysis products of hemicellulose (such as xylose, etc.) during steam explosion can be released from the raw material to a certain extent, making the content and composition of hemicellulose more stable in the subsequent processing, and making the connection between cellulose microfibrils loose, which is conducive to the formation of more evenly distributed pores. The softening and partial degradation of lignin changes its wrapping state of cellulose and hemicellulose, making the cellulose in the raw material easier to use. Moreover, this change in chemical structure reduces to a certain extent the impact of differences in chemical composition of biomass raw materials due to different sources (such as different planting environments, different varieties of plant raw materials) on product quality.
[0027] Adjustment of the pore structure of carbon materials by steam explosion: During the steam explosion process, high-temperature and high-pressure steam penetrates into the interior of the carbon material. When the pressure is released instantly, the impact force generated by the rapid expansion of the steam will cause new pores to form inside the carbon material. These new pores increase the specific surface area of the carbon material, increase its surface active sites, and are beneficial to improving the performance of the carbon material in adsorption, catalysis, etc. The strong force generated by steam explosion can expand the original smaller pores in the carbon material. On the one hand, the carbon material at the edge of the pore may be partially peeled off or stretched under the impact of steam, making the pore diameter larger; on the other hand, the thermal effect during steam explosion will also cause the structure of the carbon material to soften and deform to a certain extent, thereby promoting the expansion of the original pores, thereby improving the pore structure of the carbon material and improving its adsorption and accommodation capacity for macromolecular substances; steam explosion can make the pore distribution of the carbon material more uniform. During the explosion process, the diffusion and expansion of steam inside the carbon material is relatively uniform, which makes the pore formation and expansion degree of different parts of the carbon material tend to be consistent, thereby optimizing the pore structure of the carbon material, enabling it to more fully contact with external substances in application, improving reaction efficiency and performance stability; the impact force and thermal effect of steam explosion will also change the shape of the pores of the carbon material. Originally irregular or narrow pores may become more rounded and regular under the action of steam explosion, reducing the resistance inside the pores, increasing the diffusion rate of substances in the pores, and further improving the performance of carbon materials.
[0028] Effects of Steam Carbonization: The moisture in the material is evaporated and removed under the action of the heat provided by steam. First, free water is quickly removed, and as the temperature rises further, bound water will gradually detach from the material structure. For example, a large amount of water originally contained in biomass raw materials (such as straw, etc.) is converted into water vapor and discharged after steam heating. This process helps the subsequent carbonization reaction to proceed more efficiently and can reduce the moisture content of the subsequent carbon to a certain extent; as the temperature continues to rise, the organic components in the material begin to pyrolyze. Macromolecular organic compounds (such as lignin, cellulose, hemicellulose, etc. in biomass) will break and decompose into small molecular volatile substances (including combustible gases such as carbon monoxide, methane, hydrogen, and some organic volatiles) and solid carbon. In a steam environment, steam can play a diluting role, can promptly take away some of the volatile substances produced by pyrolysis, promote the pyrolysis reaction in the direction of generating more carbon, and also facilitate the uniform distribution of heat to prevent local overheating; when steam participates in some processes aimed at preparing carbon materials with high specific surface area and porous structure, steam also plays an activation role. High-temperature steam can react with the initially formed carbon, such as reacting with some active carbon atoms in the carbon, etching the surface of the carbon, forming more porous structures, increasing the specific surface area, and thus improving the adsorption performance and other related properties of the carbon. Commonly used in processes such as the preparation of activated carbon, the use of steam activation can make the activated carbon have a stronger ability to adsorb impurities, gases, etc.; steam fills the carbonization environment, which can squeeze out the air and reduce the chance of contact between the material and oxygen. Because if there is a large amount of oxygen during the carbonization process, the material is prone to oxidation reactions such as combustion, which is not conducive to the formation of carbon. The relatively oxygen-isolated environment formed by steam ensures that the carbonization process can proceed stably as expected, so that the material is mainly converted according to reaction pathways such as pyrolysis that are conducive to carbon formation. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a graph showing the electrical conductivity test results of the porous carbon material for the silicon-carbon negative electrode obtained in Example 1-3 and Comparative Example 1-2. DETAILED DESCRIPTION
[0030] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0031] The present invention provides a method for preparing porous carbon for silicon-carbon negative electrode material, comprising the following steps: crushing and grading, activating and forming pores, washing, and carbonizing; The method of crushing and classifying is that the pyrolysis carbonized material is crushed and classified to obtain crushed and classified material; The pyrolysis carbonized material is prepared by using biomass raw materials and / or non-biomass raw materials; The activation pore-forming method comprises: performing activation pore-forming treatment on the crushed and classified materials in the presence of activation gas in a fluidized bed device to obtain an activated pore-forming material; The washing method is to completely immerse the activated pore-forming material in hydrochloric acid or a mixed acid solution, heat the immersion, wash it to neutrality, and dry it to obtain a purified material; The carbonization method is to carbonize the purified material obtained by washing under the protection of an inert gas, control the high-temperature carbonization temperature to be not less than 1000° C., and obtain porous carbon for silicon-carbon negative electrode material.
[0032] On the basis of the above technical solution, preferably, in the crushing and grading, the particle size specifications of the crushed and graded materials are D10≥2um, D50: 5-10um, D90≤15um, and Dmax≤25um.
[0033] On the basis of the above technical solution, preferably, in the activation pore making, the activation gas is at least one of the following: water vapor, CO2.
[0034] On the basis of the above technical solution, preferably, in the activation pore making, the activation pore making temperature is 800-1100° C., and the activation pore making time is 1-5 h.
[0035] On the basis of the above technical solution, preferably, in the activation pore making, the gas linear velocity of the activation gas in the fluidized bed is controlled to be 0.05-0.5 m / s, and the fluidized bed pressure is maintained at 1-100 KPa.
[0036] On the basis of the above technical solution, preferably, in the washing, the mass fraction of the hydrochloric acid solution is 5-20%; and the mixed acid is at least two of hydrochloric acid, nitric acid, sulfuric acid, and hydrofluoric acid.
[0037] On the basis of the above technical solution, as a preferred embodiment, when the pyrolysis carbonization material is prepared by using non-biomass raw materials and / or biomass raw materials, the crushing and classification step further includes: pyrolysis carbonization; The pyrolysis carbonization method is to perform pyrolysis carbonization treatment on non-biomass raw materials and / or biomass raw materials under the protection of inert gas to obtain pyrolysis carbonized materials.
[0038] Preferably, the pyrolysis carbonization temperature is 750-850°C, the pyrolysis carbonization heating rate is 3-8°C / min, and the pyrolysis carbonization insulation time is 1-3h; more preferably, the pyrolysis carbonization temperature is 800°C, the pyrolysis carbonization heating rate is 5°C / min, and the pyrolysis carbonization insulation time is 2h.
[0039] The present invention is aimed at the situation of using non-biomass raw materials and / or biomass raw materials to prepare pyrolytic carbonized materials. A pyrolytic carbonization step is directly set before crushing and grading, and the non-biomass raw materials and / or biomass raw materials are directly subjected to pyrolytic carbonization treatment to obtain pyrolytic carbonized materials; and then the pyrolytic carbonized materials are used for subsequent crushing and grading treatment.
[0040] On the basis of the above technical solution, as a preferred parallel implementation, when the pyrolysis carbonization material is prepared by using biomass raw materials, or using biomass raw materials and non-biomass raw materials, the crushing and classification step also includes: steam explosion, pyrolysis carbonization; The steam explosion method comprises: performing steam explosion treatment on the biomass raw material in the presence of water vapor to obtain a steam-exploded material; The pyrolysis carbonization method is to perform pyrolysis carbonization treatment on the steam explosion material under the protection of inert gas to obtain the pyrolysis carbonized material; or to mix the steam explosion material with non-biomass raw materials to perform pyrolysis carbonization treatment to obtain the pyrolysis carbonized material.
[0041] Preferably, the steam explosion temperature is 170-190° C., the steam explosion pressure is 0.8-1.4 MPa, and the steam explosion pressure holding time is 5-15 min; more preferably, the steam explosion temperature is 180° C., the steam explosion pressure is 1.0 MPa, and the steam explosion pressure holding time is 10 min.
[0042] Preferably, the pyrolysis carbonization temperature is 750-850°C, the pyrolysis carbonization heating rate is 3-8°C / min, and the pyrolysis carbonization insulation time is 1-3h; more preferably, the pyrolysis carbonization temperature is 800°C, the pyrolysis carbonization heating rate is 5°C / min, and the pyrolysis carbonization insulation time is 2h.
[0043] The present invention is directed to the case where a pyrolytic carbonized material is prepared using biomass raw materials. Before crushing and grading, the biomass raw materials are first subjected to steam explosion treatment to obtain steam explosion materials; the steam explosion materials or a mixture of the steam explosion materials and non-biomass raw materials are then subjected to pyrolytic carbonization treatment to obtain pyrolytic carbonized materials; and the pyrolytic carbonized materials are then used for subsequent crushing and grading treatment.
[0044] On the basis of the above technical solution, as a preferred parallel implementation method, when the pyrolysis carbonized material is prepared by using biomass raw materials, the crushing and classification step also includes: steam carbonization and steam explosion; The steam carbonization method is to perform steam carbonization treatment on the biomass raw material in the presence of water vapor; The steam explosion method is that after the steam carbonization is completed, the steam carbonization temperature is kept unchanged, and the pressure is released to perform steam explosion to obtain the pyrolysis carbonized material.
[0045] Preferably, the steam carbonization temperature is 210-240°C, the steam carbonization pressure is 2.1-2.6 MPa, and the steam carbonization time is 40-60 min; more preferably, the steam carbonization temperature is 220°C, the steam carbonization pressure is 2.4 MPa, and the steam carbonization time is 45 min.
[0046] The present invention aims at preparing pyrolytic carbonized materials from biomass raw materials. The biomass raw materials are subjected to steam carbonization and steam explosion treatment before crushing and grading to obtain pyrolytic carbonized materials. The pyrolytic carbonized materials are then used for subsequent crushing and grading treatment.
[0047] The present invention will be further described below by way of examples, but the protection scope of the present invention is not limited to these embodiments.
[0048] Example 1 This embodiment provides a method for preparing porous carbon for silicon-carbon negative electrode material, specifically: Step 1, pyrolysis carbonization: the washed and dried coconut shell (i.e., pyrolysis carbonization raw material) is placed in a pyrolysis carbonization furnace, nitrogen is introduced as a protective gas, the temperature is increased to 800°C at a heating rate of 5°C / min, and the temperature is kept for pyrolysis carbonization for 2 hours. After naturally cooling to room temperature, the coconut shell charcoal after pyrolysis carbonization (i.e., pyrolysis carbonization material) is obtained; Step 2, crushing and grading: directly crush the coconut shell charcoal after pyrolysis and carbonization to the particle size specification of the finished porous carbon, that is, crushing to D10≥2um, D50: 5-10um, D90≤15um, Dmax≤25um, and obtaining the crushed and graded coconut shell charcoal (i.e., crushed and graded material); Step 3, activation and pore formation: 1 kg of crushed and classified coconut shell charcoal is placed in a fluidized bed, and water vapor is introduced for activation. The activation and pore formation temperature is controlled to be 1000°C, and the activation and pore formation time is 2 hours. After the activation is completed, it is naturally cooled to room temperature and then taken out to obtain the activated coconut shell charcoal (i.e., the activated pore formation material); During the activation pore-forming process, the gas linear velocity of water vapor is controlled at 0.2 m / s, and the fluidized bed pressure is maintained within the range of 30-50 KPa.
[0049] Step 4, washing: completely immerse the activated coconut shell charcoal in a 10wt% hydrochloric acid solution, heat to 80°C, keep warm and soak for 2h, wash with distilled water until the washing liquid is neutral, dry, and obtain purified coconut shell charcoal (i.e., purified material); Step 5, carbonization: Place the purified coconut shell charcoal in a carbonization furnace, introduce nitrogen as a protective gas, heat to 1100°C at a heating rate of 5°C / min, carbonize for 2 hours, cool naturally to room temperature and then take out to obtain coconut shell porous carbon (i.e., porous carbon for silicon-carbon negative electrode material).
[0050] Example 2 This embodiment provides a method for preparing porous carbon for silicon-carbon negative electrode material, specifically: Step 1, steam explosion: put the cleaned coconut shell (i.e. pyrolysis carbonization raw material) into a metal basket with dense small holes, and then put it into a steam explosion kettle, close the kettle cover and introduce steam to start steam explosion, control the steam explosion temperature to 180°C, the steam explosion pressure to 1.0MPa, the steam explosion pressure holding time to 10min, release the pressure, dry, and obtain the steam explosion material.
[0051] Step 2, pyrolysis carbonization: placing the steam explosion material in a carbonization furnace, introducing nitrogen as a protective gas, heating to 800°C at a heating rate of 5°C / min, keeping the temperature for pyrolysis carbonization for 2h, cooling naturally to room temperature and then taking it out to obtain pyrolysis carbonized coconut shell charcoal (i.e. pyrolysis carbonized material); Step 3, crushing and grading: directly crush the coconut shell charcoal after pyrolysis and carbonization to the particle size specification of the finished porous carbon, that is, crushing to D10≥2um, D50: 5-10um, D90≤15um, Dmax≤25um, and obtain the crushed and graded coconut shell charcoal (i.e., crushed and graded material); Step 4, activation and pore formation: 1 kg of crushed and classified coconut shell charcoal is placed in a fluidized bed, and water vapor is introduced for activation. The activation and pore formation temperature is controlled to be 1000°C, and the activation and pore formation time is 2 hours. After the activation is completed, it is naturally cooled to room temperature and then taken out to obtain the activated coconut shell charcoal (i.e., the activated pore formation material); During the activation pore-forming process, the gas linear velocity of water vapor is controlled at 0.3 m / s, and the fluidized bed pressure is maintained within the range of 45-65 KPa.
[0052] Step 5, washing: completely immerse the activated coconut shell charcoal in a 10wt% hydrochloric acid solution, heat to 80°C, keep warm and soak for 2h, wash with distilled water until the washing liquid is neutral, and dry to obtain purified coconut shell charcoal (i.e., purified material); Step 6, carbonization: Place the purified coconut shell charcoal in a carbonization furnace, introduce nitrogen as a protective gas, heat to 1100°C at a heating rate of 5°C / min, carbonize for 2 hours, cool naturally to room temperature and then take out to obtain coconut shell porous carbon (i.e., porous carbon for silicon-carbon negative electrode material).
[0053] Example 3 This embodiment provides a method for preparing porous carbon for silicon-carbon negative electrode material, specifically: Step 1, steam carbonization: at room temperature, put the crushed coconut shell (i.e., pyrolysis carbonization raw material) into a metal basket with dense small holes, and then put it into a steam explosion kettle, close the kettle cover and introduce steam to start steam carbonization, control the steam carbonization temperature to 220°C, the steam carbonization pressure to 2.4MPa, and the steam carbonization time to 45min; Step 2, steam explosion: after the steam carbonization is completed, the steam carbonization temperature is kept unchanged, the pressure relief valve on the steam explosion kettle is opened to perform steam explosion, and then the steam-exploded material is taken out and added into an oven for drying to obtain steam-exploded coconut shell charcoal (i.e., steam-exploded material); Step 3, crushing and grading: directly crush the coconut shell charcoal after steam explosion to the particle size specification of finished porous carbon, that is, crushing to D10≥2um, D50: 5-10um, D90≤15um, Dmax≤25um, to obtain the crushed and graded coconut shell charcoal (i.e. crushed and graded material); Step 4, activation and pore making: 1 kg of crushed and classified coconut shell charcoal is placed in a fluidized bed, and water vapor is introduced for activation. The activation and pore making temperature is controlled to be 1000°C, and the activation and pore making time is 2 hours. After the activation and pore making is completed, it is naturally cooled to room temperature and then taken out to obtain the activated coconut shell charcoal (i.e., the activated pore making material); Step 5, washing: completely immerse the activated coconut shell charcoal in a 10wt% hydrochloric acid solution, heat to 80°C, keep warm and soak for 2h, wash with distilled water until the washing liquid is neutral, and dry to obtain purified coconut shell charcoal (i.e., purified material); Step 6, carbonization: Place the purified coconut shell charcoal in a carbonization furnace, introduce nitrogen as a protective gas, heat to 1100°C at a heating rate of 5°C / min, carbonize for 2 hours, cool naturally to room temperature and then take out to obtain coconut shell porous carbon (i.e., porous carbon for silicon-carbon negative electrode material).
[0054] Comparative Example 1 The porous carbon of Comparative Example 1 was prepared using a conventional porous carbon preparation process, specifically: Step 1, pyrolysis carbonization: Place the cleaned and dried coconut shell in a carbonization furnace, introduce nitrogen as a protective gas, heat to 800°C at a heating rate of 5°C / min, keep the temperature for pyrolysis carbonization for 2h, cool naturally to room temperature and then take out to obtain coconut shell charcoal after pyrolysis carbonization; Step 2, coarse crushing: crushing the coconut shell charcoal after pyrolysis carbonization to a particle size of less than 1 mm to obtain coarsely crushed coconut shell charcoal; Step 3, activation and pore making: Place the coarsely crushed coconut shell charcoal in a rotary kiln and introduce KOH for activation. The activation and pore making temperature is 1000°C and the activation and pore making time is 4 hours. After cooling naturally to room temperature, take out to obtain activated coconut shell charcoal; Step 4, washing: completely immerse the activated coconut shell charcoal in a 10wt% hydrochloric acid solution, heat to 80°C, keep warm and soak for 2h, wash with distilled water until the washing liquid is neutral, and dry to obtain purified coconut shell charcoal; Step 5, carbonization: placing the purified coconut shell charcoal in a carbonization furnace, introducing nitrogen as a protective gas, heating to 1100°C at a heating rate of 5°C / min, carbonizing for 2 hours, cooling naturally to room temperature and then taking out to obtain coconut shell porous carbon after high temperature carbonization; Step 6, crushing and grading: Use a jet mill to crush the high-temperature carbonized coconut shell charcoal. After crushing, the porous carbon with the particle size meeting the requirements is screened out through grading, D10≥2um, D50: 5-10um, D90≤15um, Dmax≤25um.
[0055] Comparative Example 2 The porous carbon of Comparative Example 2 was prepared by using a conventional porous carbon preparation process plus fluidized bed activation, specifically: Step 1, pyrolysis carbonization: Place the cleaned and dried coconut shell in a carbonization furnace, introduce nitrogen as a protective gas, heat to 800°C at a heating rate of 5°C / min, keep the temperature for pyrolysis carbonization for 2h, cool naturally to room temperature and then take out to obtain coconut shell charcoal after pyrolysis carbonization; Step 2, coarse crushing: crushing the coconut shell charcoal after pyrolysis carbonization to a particle size of less than 1 mm to obtain coarsely crushed coconut shell charcoal; Step 3, activation and pore formation: Place the coarsely crushed coconut shell charcoal in a fluidized bed and introduce water vapor for activation. The activation and pore formation temperature is 1000°C and the activation and pore formation time is 2 hours. After cooling naturally to room temperature, take out to obtain activated coconut shell charcoal; Step 4, washing: completely immerse the activated coconut shell charcoal in a 10wt% hydrochloric acid solution, heat to 80°C, keep warm and soak for 2h, wash with distilled water until the washing liquid is neutral, and dry to obtain purified coconut shell charcoal; Step 5, carbonization: placing the purified coconut shell charcoal in a carbonization furnace, introducing nitrogen as a protective gas, heating to 1100°C at a heating rate of 5°C / min, carbonizing for 2 hours, cooling naturally to room temperature and then taking out to obtain coconut shell porous carbon after high temperature carbonization; Step 6, crushing and grading: Use a jet mill to crush the high-temperature carbonized coconut shell charcoal, and after crushing, screen out porous carbon with particle size that meets the requirements through grading. The particle size requirements of the porous carbon are D10 ≥ 2um, D50: 5-10um, D90 ≤ 15um, and Dmax ≤ 25um.
[0056] The yields of porous carbon for silicon-carbon negative electrode obtained in Examples 1-3 and Comparative Examples 1-2 were statistically analyzed, and the ash content, magnetic material, tap density, particle size D50, and pore parameters of each porous carbon for silicon-carbon negative electrode were tested. The specific results are shown in the following table:
[0057] Further, the conductivity of the porous carbon for silicon-carbon negative electrode obtained in Examples 1-3 and Comparative Examples 1-2 was tested. The specific test results are as follows: Figure 1 As shown; it can be seen that within the test temperature range, the electrical conductivity of the porous carbon for the silicon-carbon negative electrode obtained in Examples 1-3 is significantly better than that of Comparative Examples 1-2.
[0058] After the same silicon deposition and carbon coating process (silicon deposition content is 50wt%, carbon coating content is 1wt%) was performed on Example 1-3 and Comparative Example 1-2, the obtained materials were made into button half-cells using the same assembly process, and the measured electrochemical properties are shown in the following table:
[0059] It can be seen that under the same test conditions, the first coulombic efficiency of the embodiment is significantly better than that of the comparative example, which indicates that the porous carbon material prepared by the method provided by this patent also has improved terminal use performance.
[0060] Unless otherwise specified, all percentages used in the present invention are by mass.
[0061] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing porous carbon for silicon-carbon negative electrode material, characterized in that: The process includes the following steps: crushing and grading, activation and pore formation, washing and carbonization; The method of crushing and classifying is that the pyrolysis carbonized material is crushed and classified to obtain crushed and classified material; The pyrolysis carbonized material is prepared by using biomass raw materials and / or non-biomass raw materials; The activation pore-forming method is to perform activation pore-forming treatment on crushed and classified materials in a fluidized bed device in the presence of an activation gas to obtain an activated pore-forming material.
2. The method for preparing porous carbon for silicon-carbon negative electrode material according to claim 1, characterized in that: In the crushing and classification, the particle size specifications of the crushed and classified materials are D10≥2um, D50: 5-10um, D90≤15um, and Dmax≤25um.
3. The method for preparing porous carbon for silicon-carbon negative electrode material according to claim 1, characterized in that: In the activation pore making, the activation gas is at least one of the following: water vapor, CO2.
4. The method for preparing porous carbon for silicon-carbon negative electrode material according to claim 1, characterized in that: In the activation pore making, the activation pore making temperature is 800-1100° C., and the activation pore making time is 1-5 hours.
5. The method for preparing porous carbon for silicon-carbon negative electrode material according to claim 1, characterized in that: When the pyrolysis carbonization material is prepared by using non-biomass raw materials and / or biomass raw materials, the pulverization and classification step further includes: pyrolysis carbonization; The pyrolysis carbonization method is to perform pyrolysis carbonization treatment on non-biomass raw materials and / or biomass raw materials under the protection of inert gas to obtain pyrolysis carbonized materials.
6. The method for preparing porous carbon for silicon-carbon negative electrode material according to claim 1, characterized in that: When the pyrolysis carbonization material is prepared by using biomass raw materials, or using biomass raw materials and non-biomass raw materials, the crushing and classification step also includes: steam explosion, pyrolysis carbonization; The steam explosion method comprises: performing steam explosion treatment on the biomass raw material in the presence of water vapor to obtain a steam-exploded material; The pyrolysis carbonization method comprises: performing pyrolysis carbonization treatment on the steam explosion material under the protection of inert gas to obtain the pyrolysis carbonized material; or mixing the steam explosion material with non-biomass raw materials to perform pyrolysis carbonization treatment to obtain the pyrolysis carbonized material.
7. The method for preparing porous carbon for silicon-carbon negative electrode material according to claim 1, characterized in that: When the pyrolysis carbonized material is prepared using biomass raw materials, the crushing and classification step also includes: steam carbonization and steam explosion; The steam carbonization method is to perform steam carbonization treatment on the biomass raw material in the presence of water vapor; The steam explosion method is that after the steam carbonization is completed, the steam carbonization temperature is kept unchanged, and the pressure is released to perform steam explosion to obtain the pyrolysis carbonized material.
Citation Information
Patent Citations
Method for preparing active carbon by taking biomass pyrolytic carbon as raw material
CN104003387A
Method for carbonizing active giantreed carbon and pore-forming
CN1944246A
Method of obtaining granulated active carbon
RU2331580C1
Process for producing activated charcoal and the activated charcoal produced thereby
WO2022029313A1
High-nitrogen biochar composite material, preparation method therefor, and application thereof
WO2022036878A1
Cited By
Silicon-carbon composite material based on steam explosion as well as preparation method and application of silicon-carbon composite material
CN121913501A